Linking ecosystem services and measures in river and floodplain management. Issue 1 (1st January 2019) - Hornung, Lena K.; Podschun, Simone A.; Pusch, Martin
ABSTRACT: The management of rivers and floodplains is subject to multiple legal frameworks. For this reason, methods that allow a comparison of different management options are needed. Here, we apply both a literature and an expert-based approach to present an utilisable and transparent matrix approach for Central Europe, linking an array of 17 management measures with the provision of 23 ecosystem services (ESSs). In the overall matrix, 44% of the links were found to be positive or highly positive and 11% were negative or highly negative, while the other links were characterised as ambiguous or as having no effect. Overall, the effect spectra of management measures on various ESSs often indicated reduced provisioning ESSs, in particular those related to agriculture, while regulating and cultural ESSs have increased. Habitat restoration, floodplain restoration and flood risk reduction on agricultural land were the management measures that showed the most positive effects on ESSs, followed by dyke relocation. Besides the evaluation of such measures, this comprehensive approach helped to reveal knowledge gaps regarding the effects of management measures on the ESSs dealing with nutrient retention, and cultural ESSs. The matrix allows an integrative evaluation of the multifunctionality and efficiency of common management measures.EDITED BY Neville Crossman